ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK KENDARAAN BERMOTOR DI PROVINSI KALIMANTAN SELATAN - Apriliyanti, Dwi Ajeng Kartini; Harianto, Harianto; Hakim, Dedi Budiman (E-Jurnal Manajemen; Vol 10 No 4 (2021)DO - 10.24843/EJMUNUD.2021.v10.i04.p04, 2021)
Decentralization is the transfer of governmental power by the central government to autonomous regions based on the principle of autonomy. In general, the results of the analysis show that decentralization has had a positive impact on local economic growth. Global economy crisis has affect national economic growth and South Kalimantan slowdown that occurred since 2012 and continued until 2015 which only grew by 3,84%. The realization of motor vehicle tax in 2015-2019 is still fluctuating even though in certain years it has reached the target, so it is necessary to know the factors that affect the motor vehicle tax revenue. The purpose of this study was to analyze the factors that influenced motor vehicle tax revenue in South Kalimantan Province.  The types of data used in this study are primary and secondary data. The analysis method used in this research is panel data regression analysis. The results of this study showed the number of vehicles has a positive and significant effect while population, PDRB per capita, inflation, tax system haven’t significant effect on motor vehicle tax revenues in South Kalimantan Province. Keywords : Panel Data Regression Analysis, motor vehicle tax.